Microbial community dynamics in blood, faeces and oral secretions of neotropical bats in Casanare, Colombia (2024)
Bats are known reservoirs for a wide range of pathogenic microorganisms, including viruses, bacteria, fungi, helminths, and protozoa, which can be transmitted and infect other zoonotic organisms. Various studies have utilised next-generation sequencing (NGS) to describe the pathogens associated with bats. Although most have characterised microbial communities in specific body fluids, few have analysed the composition and diversity of these microbial communities across different body fluids at the individual level. In this study, we employed two next-generation sequencing techniques: amplicon-based sequencing of the V4 hypervariable region of the 16S- and 18S-rRNA genes and viral metagenomics, to describe the prokaryotic, eukaryotic, and viral communities present in blood, faeces, and oral swab samples collected from two genera of bats (Carollia and Phyllostomus) in the department of Casanare, eastern Colombia. A total of 60 samples corresponding to the three bodily fluids were processed and analysed. The results indicated that the microbial communities across the body fluids were mainly composed of bacteria, fungi, protozoa, and various DNA and RNA viruses, showing a variability of microbial genera and species. The abundances, diversity metrics, and correlations of these microorganisms displayed patterns associated with bat genus and body fluids, suggesting that the ecological characteristics of these microbial communities may be influenced by the ecological and physiological traits of the bats. Additionally, we found similar community compositions of bacteria, some fungal genera, and viruses in the three body fluids, indicating a possible circulation of these microbes within the same bat. This could be due to microbial movement from the gut microbiota to other physiological systems or transmission via blood-feeding vectors. Furthermore, our results revealed the presence of various microbes of public health concern, including Bartonella spp., Mannheimia haemolytica, Rhodotorula spp., Piroplasmida spp., Toxoplasma gondii, Alphacoronavirus spp., and Bat circovirus. The abundance of these pathogenic microbial species across the three bodily fluids suggests potential transmission routes from bats to other organisms, which may contribute to the emergence of zoonotic disease outbreaks. These findings highlight the variability of microorganisms present within the same bat and the different pathogen-host interactions that may regulate the presence and transmission of these zoonotic microbes. Further research is required to elucidate the genomic features, ecological interactions, and biological activities of these microbial communities in bats.